Chlamydia trachomatis infection in young pregnant women in Southern Brazil: a cross-sectional study - Mariângela Freitas da Silveira; Iândora Krolow Timm Sclowitz; Ludmila Gonçalves Entiauspe; Marilia Arndt Mesenburg; Dulce Stauffert; Guilherme Lucas de Oliveira Bicca; Carine Pieniz; Adriane Brod Manta
Abstract: This study estimated the prevalence of Chlamydia trachomatis infection during pregnancy in a sample of women up to 29 years of age in the city of Pelotas, Rio Grande do Sul State, Brazil, and investigated socio-demographic risk factors such as maternal age, marital status, maternal schooling, and family income. C. trachomatis infection was diagnosed with PCR using BD ProbeTecTM CT/GC Amplified DNA Assay. Socio-demographic, behavioral, and reproductive data were collected using structured questionnaires. All collections were performed by previously trained medical students. The study included a stratified probabilistic sample from four maternity hospitals in the city. The sample included 562 pregnant women, and prevalence of C. trachomatis infection was 12.3% (95%CI: 9.6-15.0). No significant association was identified between C. trachomatis infection and any of the target variables, including obstetric outcomes such as history of preterm delivery. Our findings in terms of low treatment adherence, only 43% of the women and 9.7% of partners, associated with high C. trachomatis prevalence, reinforce the need to implement routine screening for C. trachomatis during prenatal care. The attempt to diagnose and treat this infection after delivery, as in this study, limits the possibility of success.